Aluminium exposure leads to neurodegeneration and alters the expression of marker genes involved to parkinsonism in zebrafish brain. (November 2022) - Capriello, Teresa; Di Meglio, Gianluca; De Maio, Anna; Scudiero, Rosaria; Bianchi, Anna Rita; Trifuoggi, Marco; Toscanesi, Maria; Giarra, Antonella; Ferrandino, Ida
Abstract: Aluminium, despite being extremely widespread in the world, is a non-essential metal to human metabolism. This metal is known to have toxic effects on a variety of organs including the brain and is considered an etiological factor in neurodegenerative diseases. However, the molecular mechanisms by which aluminium exerts neurotoxic effects are not yet completely understood. Zebrafish is an animal model also used to study neurodegenerative diseases since the overall anatomical organization of the central nervous system is relatively conserved and similar to mammals. Adult zebrafish were exposed to 11 mg/L of Al for 10, 15, and 20 days and the neurotoxic effects of aluminium were analysed by histological, biochemical, and molecular evaluations. Histological stainings allowed to evaluation of the morphology of the brain parenchyma, the alteration of myelin and the activation of neurodegenerative processes. The expression of the Glial Fibrillary Acidic Protein, a marker of glial cells, was evaluated to observe the quantitative alteration of this important protein for the nervous system. In addition, the poly(ADP-ribose) polymerase activity was measured to verify a possible oxidative DNA damage caused by exposure to this metal. Finally, the evaluation of the markers involved in Parkinsonism was assessed by Real-Time PCR to better understand the role of aluminium in the regulation of genes related to Parkinson's neurodegenerative disease. Data showed that aluminium significantly affected the histology of cerebral tissue especially in the first periods of exposure, 10 and 15 days. This trend was also followed by the expression of GFAP. At longer exposure times, there was an improvement/stabilization of the overall neurological conditions and decrease in PARP activity. In addition, aluminium is involved in the deregulation of the expression of genes closely related to Parkinsonism. Overall, the data confirm the neurotoxicity induced by aluminium and shed a light on its involvement in neurodegenerative processes. Graphical abstract: Image 1 Highlights: Adult zebrafish were exposed to 11 mg/L Aluminium for 10, 15, and 20 days. Aluminium induced neurodegeneration mostly in organisms exposed for 10 and 15 days. The expression of GFAP protein was higher after 10 and 15 days of treatment. Al-treatment affected the expression of marker genes involved in Parkinsonism. PARP activity tended to stabilize on the 20th day of Aluminium exposure.